Appropriateness of Pediatric Orthopaedic Transfers to a Level 1 Hospital. Issue 8 (August 2018) - McKenna, Jaclyn; Novikov, David; Pawlak, Amanda; Park, Jihye; Yang, Jie; Iyer, Hariharan; Barsi, James
Abstract : Objective: To compare a cohort of transferred pediatric orthopaedic patients with orthopaedic patients who primarily presented to a Level 1 pediatric emergency department to identify risk factors for transfer. Design: Retrospective cohort study. Setting: Level 1 trauma center in New York. Patients: The cohort consisted of patients younger than 18 years who presented to 1 Level 1 pediatric trauma center between January 1, 2013, and December 31, 2013, with an orthopaedic fracture diagnosis code ( ICD-9 805.0-839.9). The control group included the patients who presented to that hospital primarily, and the study group included patients who were transferred to that same hospital from another institution. Intervention: Demographic and injury-related data [age, sex, mechanism of injury, location of injury, injury severity score, and insurance status] were collected. Main Outcome Measurements: Regression analysis was performed to assess for predictors of transfer to a Level 1 hospital. Subgroup analysis examined whether transfers were appropriate, based on the type of injury. Results: There were 1064 patients in the nontransfer group and 67 patients in the transfer group. Transferred patients were more likely to have surgery within 24 hours (39.42% vs. 2.63%) and were more likely to have no insurance or Medicaid (50.75% vs. 33.24%). Injury severity score and insurance status were independent predictors for transfer. Conclusions: This study indicates that injury severity is the primary predictor in deciding to transfer a pediatric patient; however, insurance status may play a role in that decision. Level of Evidence: Prognostic Level III. See Instructions for Authors for a complete description of levels of evidence. Abstract : Supplemental Digital Content is Available in the Text.